Action research and socio-practical organizational learning: a theoretical approach - Zwick, Elisa; Bertolin, Rosangela Violetti; Brito, Mozar José de (Revista de Administração da UFSM, 2019)
The general objective of this essay is to present an approach between the methodological perspective of action research and the organizational learning in the social practice perspective. Specifically, it aims to (i) verify action research as a methodology which purposes are, themselves, transformers of reality and (ii) demonstrate the relevance of the proposed approach to emancipatory processes, including the ethical plan. It was constructed a synopsis of the origins, the profile and the development of action research, making clear the differences between action research and classical research, as well as the reversal of the relation between subject and object, in which that becomes subject of the own knowledge and its reality, never presuming neutrality. The findings point to the uniqueness of the approach between action research and the socio-practical organizational learning process, constituting itself in a multiparadigmatic approach capable of engendering emancipation through the articulation of critical and reflection spaces. It is an approach not only restricted to technical and abstract concerns, but with emancipatory character, that needs to be integrated into the organizational studies agenda.